Stopping Macroplastic and Microplastic Pollution at Source by Installing Novel Technologies in River Estuaries and Waste Water Treatment Plants: The CLAIM Project - Gkanasos, Athanasios; Tsiaras, Kostas; Triantaphyllidis, George; Panagopoulos, Aleksandros; Pantazakos, George; Owens, Tristan; Karametsis, Christos; Pollani, Annika; Nikoli, Elisabeth; Katsafados, Nikolaos; Triantafyllou, George (Frontiers in Marine Science, 2021)
Marine pollution from debris is a major issue nowadays, since every year large amounts of terrestrial sources litter enter the sea. Addressing this problem, is fundamentally a two-fold process including litter recovery from the sea and prevention of additional pollution before entering the sea. Under the Horizon 2020 framework and within the Cleaning Litter by developing and Applying Innovative Methods in European Seas (CLAIM) project, innovative devices designed, developed, tested in laboratory conditions and applied in real conditions: An innovative device named CLEAN (CLAIM’s Litter Entrapping Autonomous Network) TRASH (Tactical River Accumulation System Hellas), coupled to an effective floating barrier installation, for the prevention of macrolitter in river estuaries before entering the Sea. A low cost, automated and self-cleaning filtering system of microplastic litter, able to retain microplastics larger than 80microns at waste water treatment plants (WWTP). The test area of the CLEAN TRASH system was the Kifissos river estuary, a significant source of terrestrial based litter for the Saronikos Gulf, for which a preliminary study of the dominant weather conditions took place, including the prevailing wind and wave patterns, as well as the seasonality of flooding events. Land based experiments showed a system efficiency of over 90% on litter above 5 mm and no “splashing” or “submerging” phenomena were observed. During sea testing period, a total amount of 1175kg of litter was collected in 38 days before entering the sea, of which the 708kg (60%) were plastic debris of various sizes and 164kg (14%) of styrofoam parts. Additionally, the filtering system was installed at the Megara WWTP. Scenarios on installing either both the CLEAN TRASH and filtering system, or standalone devices, permanently or during high rainfall periods, were performed using a 3-D coupled Hydrodynamic-Lagrangian litter tracking model. To that end, the pathways, the distribution and the accumulation areas of plastics from the above sources in the coastal area of the Kifissos River estuary and the WWTP at Megara, Attica, Greece, were studied. The potential effect on ecosystem services from further use of such devices in other river estuaries and WWTPs, is investigated.